A Critical Evaluation of the Impact of Religious Belief (Christianity) within Post-Colonial African Burial Rites: A South African Perspective - Baloyi Magezi Elijah (Religions, 2024)
The mystery of death, dying and funerals has been a universal phenomenon in the lives of almost all human beings, from humanity’s fall from grace to today. Death visits every culture, clan and family, and yet it continues to be a terrifying, unexpected stranger and the most feared enemy of human beings. People from different cultures use different coping mechanisms to fight off the pain of death, but for some people in the Collins Chabane Municipality, a particular Christian religious belief has been shown to be the most reliable asset during the battle. It is questionable whether alternative traditions besides Christianity can compete with Christianity in bringing healing from the pain of death. Various methods of healing, like African grief therapy and psychological healing, are offered to bereaved family members after death and even after burial, but are they enough for Africans to return to their normal lives? This article discusses why (Christian) religious belief is essential during and after the burial of a loved one. This is carried out within the context of colonialism having eroded all African traditions, creating a space for Christianity alone to be a remedy in death and burying.